Onde "Falha a fala. Fala a bala": discursos da violência no romance Cidade de Deus - Vieira, Ricardo Loiola (Universidade Federal de São Carlos, 2023)
Supported by the theoretical framework of Discourse Analysis, starting from the Foucaultian discursive studies, this dissertation aims to investigate the effects of meaning provoked by the discourses of violence in Cidade de Deus (2002), a novel by Paulo Lins. For that, we take as a starting point its second version – adaptation to the work, first, from 1997. We analyzed, in this way, 30 utterances extracted from passages of the book, with a view to recognizing, in this version, the installation and maintenance of discursive events of violence in the lives of subjects from the periphery. As a hypothesis, it is guided by the fact that Cidade de Deus, as a historical/documentary/literary record − since the author comes from the periphery − proposes an analysis of the way in which criminality is placed in the space of the favela and, in addition, discusses questions about cultural life there. Against the order of violence and criminality of the poor space, where the absence of the State prevails, a poetry that resists is present, a record of the beats between poetic and literary discourses from a perspective, and raw discourses − of violent reality – for another. To prove this intent, we resorted to Foucault's theoretical contribution, therefore, it is possible to place the research from three assumptions: discursive formation, utterance and subject. Therefore, possible dialogues are created, seeking, therefore, a theoretical-methodological delimitation that could contribute to the field of discourse studies. Thus, having discursiveness as an analysis tool, it would be possible to verify the mechanisms operated in the construction of narrative making, which encompasses cultural, ideological and social issues, as well as linguistic and literary ones. It also invests in its repercussions on other levels, whether cultural and/or historical-social. Through the discursive functioning of violence in the favela, we work the emergence of a peripheral voice that constitutes itself as a discursive event. That said, we think the author's constitution, the writer Paulo Lins, in the subject of discourse.
Where “the speech fails. Speak the bullet”: discourses of violence in the novel Cidade de Deus
Keywords: Cidade de Deus; Estudos Discursivos Foucaultianos; Violência; Discursividade; Criminalidade; Romance; City of God; Foucaultian Discursive Studies; Violence; Discursiveness; Criminality; Novel; LINGUISTICA, LETRAS E ARTES::LINGUISTICA